THE MEASUREMENT OF SULFATE MINERAL SOLUBILITIES IN THE NA-K-CA-CL-SO4-H2O SYSTEM AT TEMPERATURES OF 100, 150 AND 200°C - Freyer D.; Voigt W. (My University, 2004)
At T > 100°C development of thermodynamic models suffers from missing experimental data, particularly for solubilities of sulfate minerals in mixed solutions. Solubilities in Na+-K+-Ca2+-Cl--SO42-/H2O subsystems were investigated at 150, 200°C and at selected compositions at 100°C. The apparatus used to examine solid-liquid phase equilibria under hydrothermal conditions has been described.In the system NaCl-CaSO4-H2O the missing anhydrite (CaSO4) solubilities at high NaCl concentrations up to halite saturation have been determined. In the system Na2SO4-CaSO4-H2O the observed glauberite (Na2SO4 . CaSO4) solubility is higher than that predicted by the high temperature model of , especially at 200°C. At high salt concentrations, solubilities of both anhydrite and glauberite increase with increasing temperature. Stability fields of the minerals syngenite (K2SO4 . CaSO4 . H2O) and goergeyite (K2SO4 . 5 CaSO4 . H2O) were determined, and a new phase was found at 200°C in the K2SO4-CaSO4-H2O system. Chemical and single crystal structure analysis give the formula K2SO4 . CaSO4. The structure is isostructural with palmierite (K2SO4 . PbSO4). The glaserite (''3 K2SO4 . Na2SO4'') appears as solid solution in the system Na2SO4-K2SO4-H2O. Its solubility and stoichiometry was determined as a function of solution composition.